Quality Characteristics of Tomato Paste During Storage with The Addition of Citric Acid - Mamuaja, Christine F.; Helvriana, Lus (Jurnal Ilmu dan Teknologi Pangan, 2017)
Tomatoes are easily damaged due to physical, chemical and biological factors. When the production of tomato fruits is abundant, one of the handling efforts is to process tomato to become a paste.  To extend the shelf life of tomato pastes, it is added additives such as citric acid. This study aimed to determine the effect of citric acid addition to the characteristics of the tomato paste during storage. This study used factorial completely randomized design consisting of two factors, namely factor A (concentration of citric acid) and factor B (storage time) with three replications.  Tested parameters consisted of total solids, pH, vitamin C, total microbial, and organoleptic analysis. The results showed that the total solids ranged from 12.31 to 14.42%, with the lowest total solids was obtained from the treatment of citric acid addition of 0.1% at 4 weeks of storage. pH values ranged from 3.81 to 4.29, vitamin C ranged from 3.75 – 6.63 mg, and the total microbes ranged from 2.8 x 10 2 – 9.3 x 10 2 were documented on treatment of 0.1% citric acid addition at 4 weeks of storage.  From the results, it can be concluded that the addition of citric acid affected the observed parameters, the higher the concentration of citric acid the lower the total solids, pH and the total microbes.  Also during storage, it showed the increasing number of microbes, and the decreasing amount of vitamin C as well as the organoleptic value of the tomato paste.Keywords: citric acid, tomato paste, tomatoes, total microbes